Emergency department visits and inpatient hospitalizations among older patients with brain metastases: a dual population- and institution-level analysis. Issue 5 (21st May 2021) - Lamba, Nayan; Catalano, Paul J; Whitehouse, Colleen; Martin, Kate L; Mendu, Mallika L; Haas-Kogan, Daphne A; Wen, Patrick Y; Aizer, Ayal A
Abstract: Background: Older patients with brain metastases (BrM) commonly experience symptoms that prompt acute medical evaluation. We characterized emergency department (ED) visits and inpatient hospitalizations in this population. Methods: We identified 17 789 and 361 Medicare enrollees diagnosed with BrM using the Surveillance, Epidemiology, and End Results (SEER)-Medicare database (2010-2016) and an institutional database (2007-2016), respectively. Predictors of ED visits and hospitalizations were assessed using Poisson regression. Results: The institutional cohort averaged 3.3 ED visits/1.9 hospitalizations per person-year, with intracranial disease being the most common reason for presentation/admission. SEER-Medicare patients averaged 2.8 ED visits/2.0 hospitalizations per person-year. For patients with synchronous BrM (N = 7834), adjusted risk factors for ED utilization and hospitalization, respectively, included: male sex (rate ratio [RR] = 1.15 [95% CI = 1.09-1.22], P < .001; RR = 1.21 [95% CI = 1.13-1.29], P < .001); African American vs white race (RR = 1.30 [95% CI = 1.18-1.42], P < .001; RR = 1.25 [95% CI = 1.13-1.39], P < .001); unmarried status (RR = 1.07 [95% CI = 1.01-1.14], P = .02; RR = 1.09 [95% CI = 1.02-1.17], P = .01); Charlson comorbidity score >2 (RR = 1.27 [95% CI = 1.17-1.37], P < .001; RR = 1.36 [95% CI = 1.24-1.49], P < .001); and receipt of non-stereotactic vs stereotactic radiation (RR = 1.44 [95% CI = 1.34-1.55, P < .001; RR = 1.49 [95% CI = 1.37-1.62, P < .001). For patients with metachronous BrM (N = 9955), ED visits and hospitalizations were more common after vs before BrM diagnosis (2.6 vs 1.2 ED visits per person-year; 1.8 vs 0.9 hospitalizations per person-year, respectively; RR = 2.24 [95% CI = 2.15-2.33], P < .001; RR = 2.06 [95% CI = 1.98-2.15], P < .001, respectively). Conclusions: Older patients with BrM commonly receive hospital-level care secondary to intracranial disease, especially in select subpopulations. Enhanced care coordination, closer outpatient follow-up, and patient navigator programs seem warranted for this population.